(2010) Modularization of Korea's development experience : innovations in taxation policy - Jeon, Byung-Mok; Park, Sang won (KDI School of Public Policy and Management, 2011)
The Korean government has been striving to enhance transparency in all commercial transactions with the objective of achieving equity within the context of taxation. One of the keys to accomplishing such an objective is the use of an income tax deduction scheme calculated using receipts from credit card and cash transactions. Under this scheme, if a taxpayer made a payment via credit card and/or cash, that individual would be entitled to a tax deduction of a prescribed percentage of the purchased amount from their taxable income base. This scheme aims to encourage the taxpayers to actively use credit cards and cash receipts, which allow the disclosure of their transaction history to a third party, in the course of their economic activities. The ultimate goal of this scheme is to enhance transparency of income derived by businesses which provide a product or service directly to the end users. The government has been making great efforts to attain success in the operation of the credit card and cash receipts income deduction scheme, which focuses on two major strategies. Firstly, this scheme strives to establish a solid foundation supportive of the active use of credit cards and cash receipts. Even prior to the introduction of the scheme, the government devoted its energies to encourage the users to actively participate. At the launch of the scheme, the government made the scheme mandatory for the businesses of a prescribed size while pursuing the acceptance from the public with tax-based policies and various sub-mechanisms to suit different types of businesses. The outcomes of these two strategies provided the basis for other businesses to adopt the use of receipts for both the credit card and cash in the commercial transactions. The other strategy concerns with the enhancement of the public’s acceptance of the scheme by combining various policies and strategies related thereto. In addition to the incentives provided to the buyers, tax reduction was offered to the suppliers to offset the increased transaction costs and tax burden. The lottery programs simultaneously operated for those who find it difficult to meet the minimum consumption requirement (i.e. at least 10% of their total salary), preset on the expense point of view, promoted more participation in general. In addition, to prevent intentional avoidance of the scheme, the government has implemented various administrative sanctions to strengthen compliance by taxpayers including the ‘additional tax penalty program’ and the ‘reporter rewards program’. Therefore, so as to newly introduce this income deduction scheme, taking into account the two aforementioned factors, it is necessary to expand the infrastructure required in utilizing the major payment methods both before and after the implementation. In addition, appropriate economic incentives for both transaction parties in conjunction with administrative sanctions against the violators are also required. Another consideration in introducing the scheme relates to the opportunity to create supplementary schemes to enable more taxpayers to use the scheme.
Keywords: Taxation; Economic Policy